A Cross-sectional Study to Compare Hepatitis B Immunity in HIV-infected and HIV-uninfected Kenyan Children After Primary Hepatitis B Immunization. Issue 8 (August 2018) - Mbuthia, Joseph K.; Kabera, Beatrice M.; Karuga, Robinson; Ivui, Grace; Mainye, Sheila; Chanzu, Nadia Musimbi; Digolo, Lina
Abstract : To evaluate protective antibody levels against hepatitis B surface antigen in HIV-infected and HIV-uninfected Kenyan children, this study enrolled 531 children. In the HIV-infected group, only 18.3% had protective hepatitis B surface antigen compared with 74.4% in the HIV-uninfected group ( P < 0.0001). Perhaps HIV-infected children should be immunized differently.